THE OLD WORLD SPECIES OF LUDWIGIA (INCLUDING HISSIAEA), WITH A SYNOPSIS OF THE GENUS (ONAGRACEAE) - Peter H. Raven (Reinwardtia, 1963)
Evidence is presented in support of t he reduction of Jussiaea and Oocarpon to rigid. This combined genus then consists of 75 species,distributed among 17 .lions, of which Africana, Caryopkylloidea,Brenania, Seminuda, Cryptosperma, tyonia, and Miquelia are proposed in this paper, and Prieuria, N em atopy xis, Fis-docarpa, and Oocarpon are used for the first time as sections of J-udwigia. The ribution of species with pollen falling in tetrads has been compared with those rtich the grains fall singly. Of the 16 sections for which this character is known, have the pollen falling- in tetrads, five have it falling singly, and two (Micro-wm and Dantia) have both types of pollen in different species. A revision of the 23 ties of Lurhvigia in the Old World is presented, with complete synonymy; 13 hese species arc restricted to the Old World. New combinations are L. inclino.t", . L. stenorraphe subsp. speciosa, subsp. macroaepala, anil subsp. rcducta; L. pv,l-ris subsp. lobayensis is described as new; L. prostrota is delimited as a tropical icies very distinct from the temperate Asian L. epilobioides and its subsp. fjreal-(comb. nov., based on Jussiaea greatrexii); the group formerly referred to ea repens sens. lat. in the Old World is divided into three species, Ludwigia ieiis, L. stolonifera (comb, nov.), and L. pcploida (comb,nov.) with subsp. Edewsts(comb, nov.) in Australia and New Zealand (probably introduced), peploides introduced on a few Pacific Islands, and subsp. stipidacca (comb. ',) in north Asia; and named varieties of L. pedustris are regarded as ecological 'ints and reduced to synonymy. The several taxa of Madagascar described and flrded as endemic by H. Perrier de la Bathie are reduced to synonymy, leaving dagascar with no endemic taxa in this genus. Of the 13 species restricted to Old World, 8 are endemic to Africa, 4 to Asia and Malesia, and 1 is common oth regions. The genus seems to have originated in America and perhaps reached [Old World via Africa, spreading only recently to Australia, Malesia, and the lirific islands.